2022
DOI: 10.3389/fninf.2022.835657
|View full text |Cite
|
Sign up to set email alerts
|

NNMT: Mean-Field Based Analysis Tools for Neuronal Network Models

Abstract: Mean-field theory of neuronal networks has led to numerous advances in our analytical and intuitive understanding of their dynamics during the past decades. In order to make mean-field based analysis tools more accessible, we implemented an extensible, easy-to-use open-source Python toolbox that collects a variety of mean-field methods for the leaky integrate-and-fire neuron model. The Neuronal Network Mean-field Toolbox (NNMT) in its current state allows for estimating properties of large neuronal networks, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Our model can be used as a convenient template for computational studies of complex mechanisms such as the effects of neuromodulators on sensory signal processing. Being based on the LIF neuron model, mean-field analyses can provide mechanistic explanations of the population-level dynamics, and make predictions of network activities with different parameters or inputs without running simulations (Layer et al, 2022). This can help to facilitate the exploration of the effects of cell and connection properties of interneurons, and examine the hypotheses we have proposed on the main pathways underlying the suppression and enhancement of cell-type-specific activity (see Cell-Type-Specific Stimulation, Discussion).…”
Section: Discussionmentioning
confidence: 99%
“…Our model can be used as a convenient template for computational studies of complex mechanisms such as the effects of neuromodulators on sensory signal processing. Being based on the LIF neuron model, mean-field analyses can provide mechanistic explanations of the population-level dynamics, and make predictions of network activities with different parameters or inputs without running simulations (Layer et al, 2022). This can help to facilitate the exploration of the effects of cell and connection properties of interneurons, and examine the hypotheses we have proposed on the main pathways underlying the suppression and enhancement of cell-type-specific activity (see Cell-Type-Specific Stimulation, Discussion).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the NNMT gene is associated with several important physiological and disease processes. For example, the NNMT gene may play a role in energy metabolism, fatty acid oxidation, liver fat accumulation, diabetes, obesity, and cardiovascular diseases [ 50 , 51 ]. Furthermore, multiple investigations have elucidated a notable correlation between NNMT gene expression and the initiation and advancement of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The workflow is structured using snakemake ( Köster and Rahmann, 2012 ). For the mean-field analysis, we used the NNMT toolbox ( Layer et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%